2019
DOI: 10.3389/fevo.2019.00037
|View full text |Cite
|
Sign up to set email alerts
|

Recent and Projected Future Wildfire Trends Across the Ranges of Three Spotted Owl Subspecies Under Climate Change

Abstract: A major task for researchers in the twenty-first century is to predict how climate-mediated stressors such as wildfires may affect biodiversity under climate change. Previous model predictions typically did not address non-stationarity in climate-fire relationships across time and space. In this study, we applied spatially-explicit non-stationary area burned projection models to evaluate recent and future climate-driven trends in area burned across the ranges of three spotted owl subspecies in the western Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 77 publications
2
26
0
Order By: Relevance
“…Together this combination of tools provides a means to define the conditions of a desired state for a healthy ecosystem and to quantify the degree of resistance and resilience of the system to perturbation, and to measure and monitor the departure from the range of natural variability in the system dynamics. Evaluating the structure and composition of landscapes relative to historical, current and future ranges of variability is fundamental to providing context and guiding management in the face of rapidly changing climate, disturbance regimes and the resulting structure and function of ecological systems (Littell et al, 2011(Littell et al, , 2018, and their impacts on focal species (e.g., Cushman et al, 2011;Wan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Together this combination of tools provides a means to define the conditions of a desired state for a healthy ecosystem and to quantify the degree of resistance and resilience of the system to perturbation, and to measure and monitor the departure from the range of natural variability in the system dynamics. Evaluating the structure and composition of landscapes relative to historical, current and future ranges of variability is fundamental to providing context and guiding management in the face of rapidly changing climate, disturbance regimes and the resulting structure and function of ecological systems (Littell et al, 2011(Littell et al, , 2018, and their impacts on focal species (e.g., Cushman et al, 2011;Wan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Climate projections for much of western North America suggest drier weather punctuated by periods of intense precipitation resulting in more severe wildfires (Wan et al ), which could further affect spotted owl populations. Research has shown both negative and positive effects of wildfire, timber harvest, and fuels treatments on spotted owl populations (Ganey et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Climate projections for much of western North America suggest drier weather punctuated by periods of intense precipitation resulting in more severe wildfires (Wan et al 2019), which could further affect spotted owl populations.…”
Section: Spotted Owlmentioning
confidence: 99%
“…Understanding the effects of climate change may be particularly important for species that are already threatened by other factors because climate change may synergistically interact with those factors to increase their effects (e.g., Wan et al 2018, 2019). One such species is the Mexican Spotted Owl ( Strix occidentalis lucida ), one of three recognized subspecies of Spotted Owls, along with California ( S. o. occidentalis ) and Northern Spotted Owls ( S. o. caurina ; AOU 1957).…”
mentioning
confidence: 99%
“…Those threats could be exacerbated by indirect effects of climate change. In the short term, the strongest such indirect effect is likely the potential for increases in the extent and severity of fires in a warmer and drier climate (USDI FWS 2012, Wan et al 2018, 2019), but, in the longer term, indirect effects could include climate‐mediated changes in forest structure and composition.…”
mentioning
confidence: 99%